2019
DOI: 10.3390/insects10090304
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Indoor Insecticide Residue Levels after Adopting an Integrated Pest Management Program to Control German Cockroach Infestations in an Apartment Building

Abstract: Insecticide use in homes leads to human exposure to insecticide residues that persist in the environment. Integrated pest management (IPM) programs have been known to be more environmentally friendly for managing German cockroach (Blattella germanica L.) infestations, but their effect on indoor insecticide residue levels are not well understood. An IPM program consisting of applying cockroach gel baits and placing insect sticky traps as the primary treatment methods were implemented. Floor wipe samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Even compared to our restricted use of sprayable pesticides, this promotes safety when combined with the low concentration of active ingredients in the bait. Additionally, applying as much as 30 g of bait per apartment of the same type of bait used in this study did not leave toxic dust residues in a cockroach study [42]. This approach might even be considered safe with children and pets if applications are made cautiously at inaccessible locations in combination with necessary precautionary information to residents.…”
Section: Discussionmentioning
confidence: 80%
“…Even compared to our restricted use of sprayable pesticides, this promotes safety when combined with the low concentration of active ingredients in the bait. Additionally, applying as much as 30 g of bait per apartment of the same type of bait used in this study did not leave toxic dust residues in a cockroach study [42]. This approach might even be considered safe with children and pets if applications are made cautiously at inaccessible locations in combination with necessary precautionary information to residents.…”
Section: Discussionmentioning
confidence: 80%
“…The very low indoxacarb dose in the ant bait (1/12 of the cockroach bait) was sufficient to kill the primary target and appears to have produced more potent carcasses for secondary poisoning. Indoxacarb in bait formulations has also been shown to leave limited amounts of residues in cockroach-infested dwellings [27], and even lower doses in the ant bait are able to assure a very safe approach. It is also worth noting that four-week-old baits resulted in slightly higher primary mortality compared to two-week-old baits.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with most other types of pesticides, baits limit technicians' and residents' risk of exposure to harmful substances and should consequently be the method of choice against the long-tailed silverfish when control efforts are deemed necessary [21,22,27,49]. Traditional spray application may also require treatment in many rooms as the long-tailed silverfish disperse to many parts of the building or the infested dwelling [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the publication of our article [1], we found that an incorrect data set was used in the regression analysis. Figure 1 and the associated analysis results need to be changed.…”
mentioning
confidence: 99%